The Antiviral Activity of Bacterial, Fungal, and Algal Polysaccharides as Bioactive Ingredients: Potential Uses for Enhancing Immune Systems and Preventing Viruses - Chaisuwan, Worraprat; Phimolsiripol, Yuthana; Chaiyaso, Thanongsak; Techapun, Charin; Leksawasdi, Noppol; Jantanasakulwong, Kittisak; Rachtanapun, Pornchai; Wangtueai, Sutee; Sommano, Sarana Rose; You, SangGuan; Regenstein, Joe M.; Barba, Francisco J.; et al. (Frontiers in Nutrition, 2021)
Viral infections may cause serious human diseases. For instance, the recent appearance of the novel virus, SARS-CoV-2, causing COVID-19, has spread globally and is a serious public health concern. The consumption of healthy, proper, functional, and nutrient-rich foods has an important role in enhancing an individual’s immune system and preventing viral infections. Several polysaccharides from natural sources such as algae, bacteria, and fungi have been considered as generally recognized as safe (GRAS) by the US Food and Drug Administration. They are safe, low-toxicity, biodegradable, and have biological activities. In this review, the bioactive polysaccharides derived from various microorganisms, including bacteria, fungi, and algae were evaluated. Antiviral mechanisms of these polysaccharides were discussed. Finally, the potential use of microbial and algal polysaccharides as an antiviral and immune boosting strategy was addressed. The microbial polysaccharides exhibited several bioactivities, including antioxidant, anti-inflammatory, antimicrobial, antitumor, and immunomodulatory activities. Some microbes are able to produce sulfated polysaccharides, which are well-known to exert a board spectrum of biological activities, especially antiviral properties. Microbial polysaccharide can inhibit various viruses using different mechanisms. Furthermore, these microbial polysaccharides are also able to modulate immune responses to prevent and/or inhibit virus infections. There are many molecular factors influencing their bioactivities, e.g., functional groups, conformations, compositions, and molecular weight. At this stage of development, microbial polysaccharides will be used as adjuvants, nutrient supplements, and for drug delivery to prevent several virus infections, especially SARS-CoV-2 infection.